Association between serum bicarbonate levels and 28-day in-hospital mortality in dialysis patients: a multicenter retrospective cohort study based on the eICU Collaborative Research Database - Wu, Die; Liu, Yuemei; Zeng, Yueyun; Lai, Ridong; Chen, Xinglin; Wu, Dan (Frontiers in Medicine, 2025)
Background and aimsThe relationship between serum bicarbonate levels and 28-day mortality in dialysis patients remains unclear. This study aimed to investigate the association between serum bicarbonate levels and short-term mortality in patients undergoing dialysis.MethodsThis multicenter retrospective cohort study included 4,979 dialysis patients aged 18 years or older from the electronic Intensive Care Unit (eICU) Collaborative Research Database (2014–2015). Serum bicarbonate levels were measured within 24 h of ICU admission. A multivariate Cox regression model was applied to evaluate the association between serum bicarbonate levels and 28-day mortality.ResultsA total of 4,979 patients were analyzed, with a median age of 63 years. Among them, 513 patients (10.3%) died within 28 days. A significant non-linear relationship was observed between serum bicarbonate levels and mortality. Using a two-segment linear regression model, the inflection point was determined to be 30 mmol/L (log-likelihood ratio test, p = 0.029). Below this threshold, serum bicarbonate was inversely associated with 28-day mortality (OR = 0.89, 95% CI: 0.86–0.92, p < 0.0001). Above the threshold, the association was not statistically significant (OR = 1.11, 95% CI: 0.97–1.28, P = 0.1278).ConclusionSerum bicarbonate levels are non-linearly associated with 28-day mortality in dialysis patients. Levels below 30 mmol/L are linked to an increased risk of death. These findings need to be confirmed in future prospective studies.